“Candidatus Hydrogenisulfobacillus filiaventi” strain R50 gen. nov. sp. nov., a highly efficient producer of extracellular organic compounds from H2 and CO2 - Hogendoorn, Carmen; Pol, Arjan; de Graaf, Rob; White, Paul B.; Mesman, Rob; van Galen, Peter M.; van Alen, Theo A.; Cremers, Geert; Jansen, Robert S.; Jetten, Mike S. M.; Op den Camp, Huub J. M. (Frontiers in Microbiology, 2023)
Production of organic molecules is largely depending on fossil fuels. A sustainable alternative would be the synthesis of these compounds from CO2 and a cheap energy source, such as H2, CH4, NH3, CO, sulfur compounds or iron(II). Volcanic and geothermal areas are rich in CO2 and reduced inorganic gasses and therefore habitats where novel chemolithoautotrophic microorganisms for the synthesis of organic compounds could be discovered. Here we describe “Candidatus Hydrogenisulfobacillus filiaventi” R50 gen. nov., sp. nov., a thermoacidophilic, autotrophic H2-oxidizing microorganism, that fixed CO2 and excreted no less than 0.54 mol organic carbon per mole fixed CO2. Extensive metabolomics and NMR analyses revealed that Val, Ala and Ile are the most dominant form of excreted organic carbon while the aromatic amino acids Tyr and Phe, and Glu and Lys were present at much lower concentrations. In addition to these proteinogenic amino acids, the excreted carbon consisted of homoserine lactone, homoserine and an unidentified amino acid. The biological role of the excretion remains uncertain. In the laboratory, we noticed the production under high growth rates (0.034 h-1, doubling time of 20 h) in combination with O2-limitation, which will most likely not occur in the natural habitat of this strain. Nevertheless, this large production of extracellular organic molecules from CO2 may open possibilities to use chemolithoautotrophic microorganisms for the sustainable production of important biomolecules.